Thyroid Cancer & Sarcoidosis - Ergin, Ahmet Bahadir; Nasr, Christian E (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
The association of thyroid cancer and SA has been previously described in individual case reports. We are describing 4 patients with co-existence of papillary thyroid cancer (PTC) and SA who presented a diagnostic and management challenge. Patients: One patient (Patient 1) with known history of SA was referred for thyroid nodules and cervical adenopathies; Fine needle aspiration (FNA) showed PTC.  At surgery, he was found to have non-necrotizing granulomatous inflammation (NNGI) in lymph nodes in addition to PTC. Another patient (Patient 2) with known history of PTC presented with a palpable LN.  FNA showed NNGI.  She was subsequently found to have diffuse lymphadenopathies from SA. A third patient (Patient 3) who was totally asymptomatic, without history of PTC or SA, presented with a right thyroid nodule and a right lateral neck adenopathy both of which were positive for PTC. Pathology showed extensive NNGI and PTC in 4 LNs. Subsequent work up revealed diffuse lymphadenopahies throughout the body on positron-emitting tomography/computed tomography with elevated serum angiotensin converting enzyme level.  The last patient (Patient 4) who did not have any history of SA or PTC presented with systemic symptoms. Work up revealed a large goiter with substernal extension that required a thyroidectomy.  At surgery, suspicious adenopathies were resected and were found to contain NNGI.  The thyroid specimen contained PTC. Conclusion: Clinicians should be wary of this association/co-existence of SA and PTC to avoid mismanagement of neck lymphadenopathies in patients with current or history of SA. Although 4% of thyroid cancers may induce a sarcoid reaction in the thyroid gland, SA as a disease may coexist with PTC although causality remains uncertain. Being aware of this association is important in the differential diagnosis of a thyroid mass and/or a LN in a patient with SA. Therefore, patients with known SA who are found to have cervical adenopathies or thyroid nodules should have a thorough work up